Measuring the effective implementation of the GEQIP reform at school level in Ethiopia - Eryilmaz, Nurullah (Frontiers in Education, 2024)
Many educational reforms designed to improve the quality of schooling have largely been rhetorical rather than substantive in their impact on the organization of schools and classrooms around the world. In order to establish any reform, it is important to determine whether the reform is being implemented in the schools. In this sense, principals are in a critical position. Principals are responsible for enhancing student learning by implementing required changes that have repeatedly failed to increase student accomplishment. In order to determine the effective implementation of any reform, it is crucial to identify schools (low/high policy implemented schools) based on educational reform in the country. In doing so, this paper provides an example or the case of GEQIP reform implemented in Ethiopia. Quantitative data were gathered through school principal surveys. Quantitative surveys can capture different aspects of the implementation process of the reform. For this purpose, this study uses a variety of methodological strategies to develop scales and indicators based on the school principal surveys of the GEQIP reform to present the effective implementation of the GEQIP reform. This study compares the methods used to create various scales and indicators to classify schools (high/low policy implemented schools) based on the GEQIP reform, including Principal Component Analysis (PCA), Confirmatory Factor Analysis (CFA), Hierarchical Cluster Analysis, and K-Means Cluster Analysis. The paper illustrates each technique to categorise schools as high/low policy-implemented schools. The findings suggest that the implementation of GEQIP at the school level is partial and uneven, with some schools showing higher levels of implementation than others. The paper concludes by reviewing each strategy that has been used and offering information on potential future directions and discussing the implications of the findings for the successful implementation of educational reforms in Ethiopia and other similar contexts.